Implementation of repeat HIV testing during pregnancy in southwestern Kenya: progress and missed opportunities. Issue 4 (13th December 2017) - Rogers, Anna J; Akama, Eliud; Weke, Elly; Blackburn, Justin; Owino, George; Bukusi, Elizabeth A; Oyaro, Patrick; Kwena, Zachary A; Cohen, Craig R; Turan, Janet M
Abstract: Introduction: Repeat HIV testing during the late antenatal period is crucial to identify and initiate treatment for pregnant women with incident HIV infection to prevent perinatal HIV transmission and keep mothers alive. In 2012, the Kenya Ministry of Health adopted international guidelines suggesting that pregnant women be offered retesting three months after an initial negative HIV test. Our objectives were to determine the current rate of antenatal repeat HIV testing; identify successes, missed opportunities and factors associated with retesting; and estimate the incidence of HIV during pregnancy. Methods: Retrospective analysis of longitudinal data was conducted for a cohort of 2145 women attending antenatal care clinic at a large district hospital in southwestern Kenya. Data were abstracted from registers for all women who attended the clinic from the years 2011 to 2014. Results: Although 90.2% of women first came to clinic prior to their third trimester and 27.5% had at least four clinic visits, 58.0% of all women went to delivery without a retest. Missed opportunities for retesting included not returning to clinic at all, not returning when eligible, or late gestational age (>28 weeks) at first clinic visit making them ineligible for retesting (accounting for 14.2%, 26.8% and 9.6% of all clinic attendees respectively); and failure to be retested even when eligible at one or more visits (accounting for 73.2% of eligible returnees). Being unmarried and aged 20 or younger was associated with an increase in mean gestational age of first visit by 2.52 weeks (95% CI: 1.56, 3.48) and a 2.59 increased odds (95% CI: 1.90, 3.54) of failing to return to clinic, compared to those who were married and over 20 years of age. On retest, two women tested HIV positive, suggesting an incidence rate of 4.4 per 100 person‐years. After adjusting for potential confounders, only later year of last menstrual period (2013 vs. 2012 and 2011) was associated with retesting. Conclusions: Adoption of retesting guidelines in 2012 appears to have successfully increased retesting rates, but missed opportunities to identify incident HIV infection during pregnancy may contribute to continuing high rates of perinatal HIV transmission in southwestern Kenya.